Salvage autologous stem cell transplantation for multiple myeloma relapsing or progressing after up-front autologous transplantation. Issue 10 (October 2013) - Auner, Holger W.; Szydlo, Richard; Rone, Alero; Chaidos, Aristeidis; Giles, Chrissy; Kanfer, Ed; Macdonald, Donald H.; Marin, David; Milojkovic, Dragana; Pavlu, Jiri; Apperley, Jane F.; Rahemtulla, Amin
Abstract Progression or relapse occurs in the vast majority of patients with multiple myeloma (MM) who undergo up-front autologous hematopoietic cell transplantation (AHCT1), which remains a cornerstone of treatment in the era of novel agents. Limited data are available regarding the value of salvage therapy with a second AHCT (AHCT2) in patients who relapse/progress after AHCT1. We analyzed the outcome of 83 patients who underwent salvage AHCT2 between 1994 and 2011. Most patients (77%) had received treatment with novel agents between AHCT1 and AHCT2, and 28% of patients were from ethnic minority groups. Median overall survival (OS) from AHCT2 was 31.5 months (95% confidence interval [CI]: 22–41), and median progression-free survival (PFS) was 15.5 months (95% CI: 11–20). In multivariate analysis, only disease status (≥ PR) at AHCT2 was associated with better OS. The 3-year OS rates for patients receiving AHCT2 in > PR and PR were 85.9% (95% CI: 61–96) and 51.3% (95% CI: 34–68), respectively. Disease status at AHCT2 and time to progression/relapse after AHCT1 were associated with PFS in multivariate analysis. In summary, salvage AHCT2 is an effective treatment option in patients with chemosensitive relapse/progression and prolonged remission after a prior autograft.